Catheads in the cradle: A ten-month old girl with a subglottic cathead burr. (September 2017) - Holmes, Timothy; Mohammadi, Aydin; Houghton, David
Abstract: We present the case of a young girl with a cathead burr impacted in her subglottis. Novel means were required to extract it, and her case highlights logistical and technical difficulties in managing paediatric foreign body aspiration in regional areas.